The techniques of political agenda setting by bloggers: a look at Che’ Det.Com and Raja Petra Kamaruddin’s blogs / Mazril Hameedy Mazlan and Mariah Muda - Mazlan, Mazril Hameedy; Muda, Mariah (CMIWS and UiTM Press, 2010)
The aim of this study is to analyze alternative media such as blogs in order to understand its content, intention, and look at the impact it has on readers. The general objective of this research is to look at the content of two most popular blogs in Malaysia regarding the “Perak crisis”. The study explored the writing style of bloggers based on the Agenda Setting Theory. The research design is quantitative in nature involving data which were content analyzed from the blogs of Tun Mahathir and Raja Petra Kamarudin. Results show that che det. com made his readers to reject party jumping from his experience as an ex-Prime Minister’s point of view as he was more worried about the image or perception the general public would have if the Barisan Nasional or specifically UMNO was to accept party jumpers. On the other hand, Raja Petra is agenda in his blog was clearly to highlight the incompetence of Parti Keadilan Rakyat in handling the issue as he pointed out that the issue has been brewing for a while and the party leaders failed to take affirmative action. The difference and the implications of the blog readers giving different feedbacks in both blogs could be contributed by demographics of the readers themselves. This study also revealed that both blogs identified UMNO as the victim as both blogs attributed the Perak Crisis with the power play and intervention of UMNO. Same thing goes to readers where they also criticized UMNO as the main player in the crisis. However, it is worth mentioning that there was also blog readers who sympathized with UMNO. Their study suggested that the blog writers were successful in making the readers think what to think about. This study contributes to the knowledge about how the blogs are now important in shaping the minds of the people especially in the discussion of local politics.